Credit constraints, entrepreneurial talent, and economic development - Milo Bianchi (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2009)
In this paper, we formalize the view that economic development requires high rates of productive entrepreneurship, and this requires an efficient matching between entrepreneurial talent and production technologies. We first explore the role of financial development in promoting such efficient allocation of talent, which results in higher production, job creation and social mobility. We then show how different levels of financial development may endogenously arise in a setting in which financial constraints depend on individual incentives to misbehave, these incentives depend on how many jobs are available, and this in turn depends on the level of financial development. Such complementarity between labour market and financial market development may generate highly divergent development paths even for countries with very similar initial conditions.
Keywords: J24; L26; O16; 330; credit constraints; allocation of entrepreneurial talent; productive and unproductive entrepreneurs; economic development; Entrepreneurship-Ansatz; Berufswahl; Fertigungstechnik; Verschuldungsrestriktion; Entwicklung